Cobertura mediática de los movimientos sociales en los medios impresos de Riobamba, periodo julio - diciembre 2024. - Contero Parco, Gilson David (2026)
Social movements are collective demonstrations that, over time, have become a relevant topic in the media agenda. With the emergence of print media, these movements have received greater coverage, and their actions have reached more people. In this sense, the main objective of this research is to analyze the print media coverage of social movements in Riobamba from July to December 2024. This research employs a qualitative, descriptive approach to collect data on the media coverage provided by Riobamba's print media in their digital publications. The topics covered were analyzed using observation sheets, which showed that the daily newspaper La Prensa provides equitable coverage of different social groups, with news focused on neighborhood groups, indigenous peoples, and entrepreneurs, while migratory, feminist, and animal rights movements are covered two or three times a month. For its part, Los Andes provided greater coverage of indigenous, transport, and neighborhood movements, while movements such as retirees and migrants received minimal coverage. The LGBTQIA+ movement received only one piece of coverage, from La Prensa.